One-phase Transesterification of Palm Oil in to Biodiesel with Co-solvent Methyl Esters: The Effect of Adding Co-solvent to Kinetic Energy and Dipole Moment - Elvianto Daryono; Lalu Mustiadi (Reaktor, 2022)
In the transesterification process, the problem is the low solubility of oil in methanol, so the reaction will run slowly. The solution to this problem is to add a co-solvent to increase the solubility so that a one-phase reaction will be formed. The co-solvent methyl ester is the right choice because it is a product of the reaction itself so that it does not require a separation process. The operating conditions of the study were mass of palm oil 250 g, mass of NaOH catalyst 0.8%wt, stirring speed 100 rpm, reaction temperature 60oC, the molar ratio of oil:methanol = 1:6, reaction time (5,10,15,20,25,30 minutes), and the mass of co-solvent (0,5,10,15%wt). The first stage of the research was to make co-solvent, then proceed with the transesterification reaction by adding  co-solvent which was carried out according to the research operating conditions. The optimum condition of the study was obtained at reaction time 30 minutes and the addition of co-solvent 5%, with yield 97.4171%. The density of FAME 0.88 g/mL and the concentration of FAME 99.963% which complied with SNI 7185-2015. The simulation results of ChemDraw for components of triglyceride+methanol+NaOH+co-solvent obtained kinetic energy 3479.0264 kJ/mol and dipole moment 43279.8007 debyes.